Increased Fertilization Rates after In Vitro Culture of Frozen-Thawed Testicular Immotile Sperm in Nonobstructive Azoospermic Patients. (5th March 2012) - Nuñez-Calonge, R.; Cortes, S.; Gago, M.; López, P.; Caballero-Peregrin, P.
Abstract : Objective . To optimise the use of freeze/thaw testicular immotile spermatozoa from nonobstructive azoospermia patients and to analyse the outcome of intracytoplasmic sperm injection (ICSI) of such spermatozoa. Methods . Testicular specimens were retrieved and cryopreserved from forty patients with nonobstructive azoospermia and underwent one cycle with thawed spermatozoa (Group I) that led to pregnancy in sixteen cases. Twenty-four patients of group I underwent treatment with the same batch of thawed spermatozoa (Group II). For the first ICSI attempt, injection was performed when motile spermatozoa were found. In group II, injection was performed when maximum motility was reached. We compared mean of fertilization rate, embryo quality, clinical pregnancy rate and embryo implantation rate. Results . The mean percentage of motility was significantly higher in the group II than in the group I (18, 6 versus 8, 2). Group I showed a significant decrease in fertilization rates when compared with cryopreserved testicular spermatozoa in group II (54% versus 72%, P < 0.05 ). No difference was noted between the cleavage rate, embryo quality, clinical pregnancy rates and implantation rates among group II and I. Conclusion . Fecundation rate can be significantly improved after in-vitro culture and sperm selection of frozen-thawed immotile testicular spermatozoa in patients with nonobstructive azoospermia.